A Rare Case of Glioblastoma Multiforme with Osseous Metastases - Rubens Barros Costa; Ricardo Costa; Jason Kaplan; Marcelo Rocha Cruz; Hiral Shah; Maria Matsangou; Benedito Carneiro (Case Reports in Oncological Medicine)
Glioblastoma multiforme is the most common malignant primary central nervous system neoplasm in adults. It has a very aggressive natural history with a median overall survival estimated at 14.6 months despite multimodality treatment. Extracranial metastases are very rare with few case reports published to date. We report the case of a 65-year-old male who underwent maximal safe resection for a newly diagnosed brain mass after presentation with new neurologic symptoms. He then received standard postsurgical adjuvant treatment for glioblastoma. Subsequently, he underwent another resection for early progressive disease. Several months later, he was hospitalized for new-onset musculoskeletal complaints. Additional investigation revealed new metastatic osseous lesions which were initially felt to be a new malignancy. The patient opted for supportive care and died 12 days later. Despite choosing no treatment, he elected to undergo a bone biopsy to understand the new underlying process. Results were that of metastatic GBM and were reported after the patient expired. Physicians caring for patients with GBM and new nonneurologic symptoms may contemplate body imaging.